Crosstalk between Phospholipase D and Sphingosine Kinase in Plant Stress Signaling - Wang, Xuemin (Frontiers in Plant Science, 2012)
The activation of phospholipase D (PLD) produces phosphatidic acid (PA), whereas sphingosine kinase (SPHK) phosphorylates long-chain bases (LCBs) to generate LCB-1-phosphates (LCBPs) such as phytosphingosine-1-phosphate (phyto-S1P). PA and phyto-S1P have been identified as lipid messengers. Recent studies have shown that PA interacts directly with SPHKs in Arabidopsis, and that the interaction promotes SPHK activity. However, SPHK and phyto-S1P act upstream of PLDα1 and PA in the stomatal response to abscisic acid (ABA). These findings indicate that SPHK/phyto-S1P and PLD/PA are co-dependent in the amplification of lipid messengers, and that crosstalk between the sphingolipid- and phospholipid-mediated signaling pathways may play important roles in plant stress signaling.